The anticipatory and task-driven nature of visual perception - Uithol, S; Bryant, KL; Toni, I; Mars, RB (Oxford University Press, 2021)
Humans have a remarkable capacity to arrange and rearrange perceptual input according to different categorisations. This begs the question whether the categorisation is exclusively a higher visual or amodal process, or whether categorisation processes influence early visual areas. To investigate this we scanned healthy participants in a magnetic resonance imaging scanner during a conceptual decision task in which participants had to answer questions about upcoming images of animals. Early visual cortices (V1 and V2) contained information about the current visual input, about the granularity of the forthcoming categorical decision, as well as perceptual expectations about the upcoming visual stimulus. The middle temporal gyrus, the anterior temporal lobe, and the inferior frontal gyrus were also involved in the categorical decision, constituting an attention and control network that modulates perceptual processing. These findings provide further evidence that early visual areas process visual input according to conceptual expectations and task demands.